The Impact of TikTok Educational Content Project-Based Method on Comprehension of Algorithm Strategy Material for 11th Grade Students at SMAN 1 Gunung Talang - Mubarokah, Hudiya; Delianti, Vera Irma (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
Informatics learning for grade XI requires a strong understanding of algorithm strategies to develop students' logical thinking abilities. The Project-Based Learning (PjBL) method applied by teachers often pays insufficient attention to the learning process, making it less attractive to Generation Z students who are accustomed to fast visual content like TikTok. This condition causes students to regard algorithm strategies as difficult and irrelevant material. This research aims to examine the effect of TikTok educational content projects in improving grade XI students' understanding at SMAN 1 Gunung Talang regarding algorithm strategy material. The research uses a quantitative method with a quasi-experimental design. The research population consists of all grade XI students at SMAN 1 Gunung Talang with a sample of 60 students selected using purposive sampling. Data collection was conducted through tests using Google Forms. Data analysis includes normality, homogeneity, and hypothesis testing using SPSS 21. The Lilliefors normality test results show Lo(calculated) 0.095 (experimental) and 0.093 (control) < Lt(table) 0.159, indicating normally distributed data. The homogeneity test yielded a significance of 0.962 > 0.05 (homogeneous). The t-test shows sig (2-tailed) 0.000 < 0.05, proving there is a significant difference between PjBL with TikTok content and PjBL in improving understanding of algorithm strategies.